Trends and Future Outlook for Mobile Application Development Using Design Thinking Approach: A Systematic Literature Review - Saputra, Prasetya Cahya; Ramadhan, Arief (ULTIMA InfoSys, 2024)
In today's technological world, mobile-based application development has become a crucial and integral element for achieving competitive advantage. Various fields have tried to create mobile applications. One widely used method is Design Thinking, which focuses on creating more innovative, user-focused, and contextual solutions. This writing reviews mobile application development using the Design Thinking approach as the main method. In this research, the author explores the basic principles of Design Thinking, its processes, and how they can be applied effectively in the stages of mobile application development. The authors also analyze the benefits derived from this approach, including improved product quality, positive user response, and the potential to meet changing market needs. The results illustrate that the Design Thinking approach is not just an application development tool, but also a philosophy that drives better innovation and more relevant solutions. This SLR will display research results to what extent the Design Thinking approach in mobile application development has been used.